Dogs decoded [videorecording (DVD)] : understanding the human-dog relationship - Child, Dan (PBS Distribution, 2010)
Dogs have been domesticated for longer than any other animal on the planet, and humans have developed a unique relationship with these furry friends. New research is revealing what dog lovers have suspected all along, that dogs have an uncanny ability to read and respond to human emotions. How did this incredible relationship between humans and dogs come to be? And how can dogs, so closely related to fearsome wild wolves, behave so differently? It's all in the genes.